Extremely Sensitive, Allochroic Airflow Sensors by Synergistic Effect of Reversible Water Molecules Adsorption and Tunable Interlayer Distance in Graphene Oxide Film. Issue 9 (8th April 2019) - Huang, Yinan; Wang, Shuguang; Wang, Zhongwu; Gong, Xu; Meng, Yancheng; Li, Hongwei; Tan, Ziting; Yuan, Liqian; Li, Jie; Chen, Yigang; Li, Liqiang; Hu, Wenping
Abstract: In nature, the accurate flow sense of skin or hair gives the creatures incredible power for flight control and escaping danger, which stimulates the vigorous pursuit for the construction of extremely sensitive artificial airflow sensor. Here, inspired by the nasal skin and chameleon, a kind of extremely sensitive, allochroic airflow sensor is developed based on graphene oxide (GO) sheets, which senses airflow with dual output signals (current and color) by synergistic effect of reversible water molecules adsorption and tunable interlayer distance. This kind of sensor demonstrates extremely high sensitivity (i.e., huge conductivity changes of several orders of magnitude), a response time of about 1 s, and a detection limit as low as 0.2 mm s −1 that is even lower than the detection limit of human skin. Remarkably, just like the chameleon changes color by tuning the guanine nanocrystal lattice, this sensor achieves the impressive color changing ability via tunable interlayer distance under gas flow, which implies its potential application for the visualized airflow sensors. Abstract : Inspired by the nasal skin and chameleon, a kind of extremely sensitive, allochroic airflow sensor based on graphene oxide (GO) sheets is developed, which senses airflow with dual output signals (current and color) by synergistic effect of reversible water molecules adsorption and tunable interlayer distance. The detection limit of this sensor surpasses human skin.